The glow of unwork? Issues of portrayal in networked learning research - Savin-Baden, Maggi; Tombs, Gemma (Proceedings of the International Conference on Networked Learning, 2016)
In this paper, we suggest that portrayal of research is often undervalued and seen as ‘unwork’ (Galloway, 2012). Portrayal is often seen as an issue that is relatively straight forward by qualitative researchers, and invariably refers to putting the findings of the study together with excerpts from participants and usually, but not always, some interpretation. It tends to be seen as the means by which the researcher has chosen to position people and their perspectives, and it is imbued with a sense of not only positioning but also a contextual painting of a person in a particular way. Yet there are an array of issues and challenges about what portrayal can or might mean in digital spaces. In this paper we argue that researching education in a digital age provides greater or different opportunities to represent and portray data differently and suggest that these ways are underutilised. For example, for many researchers legitimacy comes through the use of participants’ voices in the form of quotations. However, we argue that this stance towards plausibility and legitimacy is problematic and needs to be reconsidered in terms of understanding differences in types of portrayal, recognizing how researchers position themselves in relation to portrayal, and understanding decision-making in relation to portrayal. We suggest that there need to be new perspectives about portrayal and concept, and ideas are provided that offer a different view. Three key recommendations are made: 1. Portrayal should be reconceptualised as four overlapping concepts: mustering, folding, cartography, and portrayal. Adopting such an approach will enable audiences, researchers and other stakeholders to critique the assumptions that researchers on tour bring to portrayal and encourage reflexivity. 2. Researchers on tour should highlight the temporal, mutable and shifting nature of portrayed research findings, emphasising the need for continued and varied research to inform understanding. 3. There is a significant need for greater insight into the influence of portrayal, as well as the difference between representation and portrayal. Future studies should prioritise this, and ensure that portrayal is considered and critiqued from the outset.